Study on Appraisal of Animal Health Constraints along the Dairy Value Chains in Kenya - John A. Kidali; T. Karanja; E. O. Mungube; M. W. Maichomo; J. C. Njanja; J. M. Mugambi; E. Thuranira; F. M. Muriithi; L. W. Wamae; S. O. Nyamwaro (Current Topics in Agricultural Sciences Vol. 2, 2021)
The research was conducted in Nairobi, Kiambu, Kericho, Kilifi, and Uasin Gishu counties. The study’s overarching goal was to identify and record the obstacles that prevent dairy value chains from being managed effectively. The identification of restrictions will aid in the development of strategies to increase dairy productivity and profitability. A stakeholder survey among the value chain stage actors gathered primary and secondary data, yielding the following results: Research institutions and vaccine producers experienced constraints at institutional levels that impacted on the effective animal health management. Agro-vets were important contact points for livestock sector participants and hence have the capacity to disseminate animal health information messages. Some of the Agro-vets were run by non-professionals, lacked suitable drug storage facilities, sold illegal substandard pharmaceuticals, had limited input capital, and had exorbitant interest rates on loans, all of which affected their ability to operate. 33 counties were served by the three Regional Veterinary Investigation Laboratories (VILs) that were visited. Those near VILs submitted more samples for testing than counties further away. Over the course of 11 years, 45,040 samples were collected, with 6,971 in Eldoret, 11,975 in Kericho, and 26,091 in Mariakani. The top ten disorders diagnosed accounted for more than 85% of the total. Mastitis was the most common problem, accounting for 41.9 percent of all cases, followed by ECF at 10.6 percent and nematodes at 4.5 percent.